(untitled) (Fiep Bulletin - online, 2014)
We live today in education , a new time: the time of inclusion. Ie , leave no student Carrier Special Needs out of school , and more specifically , outside the regular school . However , inclusion does not mean just put these students in regular classes but also ignore that are unique beings with characteristics , needs and interests . The article challenges : Inclusion and Physical Education in Elementary Education highlights the literature on inclusive education that the attitudes of teachers towards students placed in the classroom depends heavily on factors such as type of society in which it operates school : conceptions and representations social on disability , difference , diversity , learning disabilities and the resources and mechanisms of functioning of schools and educational management policies , and considering teacher training are the most pressing agendas that should go on the agenda for research and educational policy . It is understood that the proposal inclusive in Brazil is going through major challenges: training courses , a different look to meet real needs . However , we have failed to make an inclusive education that can provide quality students , and she turned to cognitive - socio- cultural development of students. This paper will report on the experience of the challenges of inclusion of students with Special Needs with the discipline of Physical Education , highlighting the difficulties and the progress the school community who experience the learning process along with the inclusion process .